2013
DOI: 10.1017/etds.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic properties of -adic Halton sequences

Abstract: We investigate a parametric extension of the classical s-dimensional Halton sequence, where the bases are special Pisot numbers. In a onedimensional setting the properties of such sequences have already been investigated by several authors [5,8,23,28]. We use methods from ergodic theory to in order to investigate the distribution behavior of multidimensional versions of such sequences. As a consequence it is shown that the Kakutani-Fibonacci transformation is uniquely ergodic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…This sequence, also called Kakutani-Fibonacci sequence, has been also analysed in detail in [5,9] in the frame of ergodic theory where it has been shown that it can be obtained as the orbit of an ergodic transformation.…”
Section: Discrepancy Bounds For Classical Ls-sequencesmentioning
confidence: 99%
“…This sequence, also called Kakutani-Fibonacci sequence, has been also analysed in detail in [5,9] in the frame of ergodic theory where it has been shown that it can be obtained as the orbit of an ergodic transformation.…”
Section: Discrepancy Bounds For Classical Ls-sequencesmentioning
confidence: 99%
“…In particular, when L = S = 1, the Kakutani-Fibonacci (1, 1)-sequence coincides with the β-adic van der Corput sequence where β = Φ is the golden ratio, i.e. the positive root of x 2 − x − 1 (see also [18] for more details). β-adic sequences and L S-sequences provide, in dimension 1, low-discrepancy sequences.…”
Section: Introductionmentioning
confidence: 89%
“…They have been studied quite extensively. For good references on the subject we suggest [3,18,22,23]. For the original definition of van der Corput sequence see [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting here that the van der Corput sequence and some one-dimensional low-discrepancy sequences with respect to the Cantor expansion were studied in [2] and [5]. Note also that it was mentioned in [8] about the Halton sequence in a more generalized numeration system than the Cantor expansion, called the G-expansion; however, the paper aimed to study the Halton sequence in some fixed non-integer bases and did not touch on the Halton sequence with respect to dynamical bases.…”
Section: Introductionmentioning
confidence: 99%